2022
DOI: 10.1002/jpln.202100437
|View full text |Cite
|
Sign up to set email alerts
|

Soil health, soil genetic horizons and biodiversity#

Abstract: Maintaining or recovering soil health is becoming a goal of many policies carried out at national, continental and global scales to promote global health. This viewpoint is aimed at stressing the relevance of a holistic approach to soil health assessment and monitoring, which is not only related to soil functional biodiversity but also considers the genetic horizons of the soil profile and not just the topsoil. We highlight that soil health has different connotations depending on the environmental setting and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 74 publications
1
15
0
Order By: Relevance
“…This is one of the alarming omissions in our understanding of soil biodiversity that should be addressed in the future. However, several studies have shown that different pedotaxa types (Garbeva et al, 2004;Fierer and Jackson, 2006;Gagelidze et al, 2018) and different soil horizon types (Ekelund et al, 2001;Fierer et al, 2003;Rosling et al, 2003;Hansel et al, 2008;Doblas-Miranda et al, 2009;Eilers et al, 2012;Costantini and Mocali, 2022) house different assemblages of soil organisms, which indicates soil horizons should be considered in defining the variety of habitats utilized by soil organisms. It has been demonstrated that geographical spaces with low pedodiversity are also poor in above-ground biodiversity (see Ibáñez and Bockheim, 2013;Ibáñez, 2017;and chapters therein;Rillig et al, 2019).…”
Section: Biodiversity and Pedodiversity Versus Geodiversity: Two Dive...mentioning
confidence: 99%
“…This is one of the alarming omissions in our understanding of soil biodiversity that should be addressed in the future. However, several studies have shown that different pedotaxa types (Garbeva et al, 2004;Fierer and Jackson, 2006;Gagelidze et al, 2018) and different soil horizon types (Ekelund et al, 2001;Fierer et al, 2003;Rosling et al, 2003;Hansel et al, 2008;Doblas-Miranda et al, 2009;Eilers et al, 2012;Costantini and Mocali, 2022) house different assemblages of soil organisms, which indicates soil horizons should be considered in defining the variety of habitats utilized by soil organisms. It has been demonstrated that geographical spaces with low pedodiversity are also poor in above-ground biodiversity (see Ibáñez and Bockheim, 2013;Ibáñez, 2017;and chapters therein;Rillig et al, 2019).…”
Section: Biodiversity and Pedodiversity Versus Geodiversity: Two Dive...mentioning
confidence: 99%
“…However, both natural factors such as climate, parent material, vegetation, time, and topography, as well as anthropogenic factors such as cultivation, grazing, and construction, influence soil diversity. This complexity, thus, renders the concept and measurement of soil diversity quite intricate [15][16][17]. In the 1990s, Ibáñez et al [18] proposed the use of ecological research methods for analyzing the category diversity of soils within the pedosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Soils in all natural and managed environments exhibit spatial and temporal heterogeneity ( Lechowicz and Bell, 1991 ; Day et al., 2003a ; Mommer et al., 2012 ; Zhou et al., 2012 ; Costantini and Mocali, 2022 ). Clonal plants exhibit foraging responses to efficiently capture heterogeneous resources in soil, showing morphological plasticity or localized physiological changes in microsites with different nutrient levels ( Hodge, 2004 ; Dong et al, 2015a ; Dong et al, 2015b ).…”
Section: Introductionmentioning
confidence: 99%